Volume 2: Simple and Combined Cycles; Advanced Energy Systems and Renewables (Wind, Solar and Geothermal); Energy Water Nexus; 2014
DOI: 10.1115/power2014-32169
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Combined Heat and Power Systems for Offshore Oil and Gas Facilities With CO2 Bottoming Cycles

Abstract: In this work different concepts are investigated for combined heat and power production (CHP) from offshore gas turbines. Implementation of such technology could improve energy efficiency of offshore oil and gas production and lead to reduced fuel consumption and resulting CO2 emissions. Offshore electric power is in most cases generated by gas turbines operating in a simple cycle. However it would be desireable to increase energy efficiency by adding steam or CO2 bottoming cycles to produce power from the exh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Since the Norwegian electric power system is mostly based on hydropower generators, decarbonization solutions are required in other areas of the Norwegian economy. Previous research has indicated that installation of off-shore bottoming cycles can reduce up to 25% of CO 2 emissions from an off-shore platform (Nord and Bolland 2012;Mazzetti et al, 2014a). This solution could contribute to Norway's goal of 40% reduction in CO 2 emissions from 1990 to 2030 and also toward the goal of net zero emissions by 2050.…”
Section: Introductionmentioning
confidence: 99%
“…Since the Norwegian electric power system is mostly based on hydropower generators, decarbonization solutions are required in other areas of the Norwegian economy. Previous research has indicated that installation of off-shore bottoming cycles can reduce up to 25% of CO 2 emissions from an off-shore platform (Nord and Bolland 2012;Mazzetti et al, 2014a). This solution could contribute to Norway's goal of 40% reduction in CO 2 emissions from 1990 to 2030 and also toward the goal of net zero emissions by 2050.…”
Section: Introductionmentioning
confidence: 99%
“…With lower power demand from the gas turbine, less heat is available to the bottoming cycle. It can, for example, be 70% of on-design exhaust heat at 50% load for a gas turbine [11], or 50% of on-design exhaust heat at 20% load for other gas turbine types [12]. The value depends on the gas turbine type and how it is controlled, but it typically falls near mentioned values.…”
Section: Introductionmentioning
confidence: 99%
“…However, significant room for improvements was identified as other concepts showed potential to achieve better performance [4]. Efficiency improvements were identified as a sustainable option to simultaneously satisfy economics and energy security as well as the environmental objectives [5]. Considering the thermodynamic performance of petroleum platforms, efficiency increase is achievable through improving the performance of the processing plant, e.g.…”
Section: Introductionmentioning
confidence: 99%